2012
DOI: 10.1155/2012/835464
|View full text |Cite
|
Sign up to set email alerts
|

Women's and Midwives' Perspectives on the Design of a Text Messaging Support for Maternal Obesity Services: An Exploratory Study

Abstract: This study was aimed to explore women's and midwives' views on the use of mobile technology in supporting obese pregnant women with healthy lifestyle choices. A purposive sample of 14 women and midwives participated in four focus groups in Doncaster, UK. A content analysis of the transcripts from the first focus group led to the emergence of three main constructs with associated subcategories including Benefits (“modernising,” “motivating,” “reminding,” and “reducing” the sense of isolation), Risks and Limitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
76
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(82 citation statements)
references
References 38 publications
6
76
0
Order By: Relevance
“…Just in case I'm not meant to be going to the gym and things" (Julie, Parity 1, BMI 30kg/m 2 ) Discussion Participants reported an overall positive experience of attending a dietetic service in pregnancy, identified aspects of the service they felt were particularly helpful and some areas for service improvement relating to referral, delivery and content of the service. Other studies have shown an overall positive experience of antenatal weight management support (Soltani et al, 2012;Fealy et al, 2014;. However, there were two women whose discussions were predominantly negative.…”
Section: Resultsmentioning
confidence: 79%
“…Just in case I'm not meant to be going to the gym and things" (Julie, Parity 1, BMI 30kg/m 2 ) Discussion Participants reported an overall positive experience of attending a dietetic service in pregnancy, identified aspects of the service they felt were particularly helpful and some areas for service improvement relating to referral, delivery and content of the service. Other studies have shown an overall positive experience of antenatal weight management support (Soltani et al, 2012;Fealy et al, 2014;. However, there were two women whose discussions were predominantly negative.…”
Section: Resultsmentioning
confidence: 79%
“…We identified 21 studies reported in 26 papers that reported service‐user views on WMPs (see Figure for PRISMA figure presenting flow of studies through the review). The 21 studies reported the views of 507 service users, and there was a good range in terms of gender, age and socio‐economic status, but limited data from minority‐ethnic service users; just one study focused on a programme specifically for a minority‐ethnic group and most others which provided information on the ethnicity of participants stated that they were predominantly white British.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have examined the efficacy of evidencebased theories for developing posts using Motivational Interviewing [12] and social cognitive theory [8] for internet-and social media-based interventions. In addition, qualitative studies have examined what types of posts participants preferred receiving in the context of a weight loss intervention (such as motivating, planning, overcoming barriers, and prompting for self monitoring) [13]. However, previous studies have not examined what types of posts most engage participants in social media-based interventions, and if this engagement, in turn, promotes weight loss.…”
Section: Introductionmentioning
confidence: 99%